Circular Economy: Product Recycling and Social Effects Case Study: Safina Quilt Balikpapan - Rahajeng Cahyaning Putri Cipto; Sudarmiatin Sudarmiatin; Puji Handayati; Naswan Suharsono (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study explores the implementation of circular economy principles within Safina Quilt, an MSME in Balikpapan that transforms textile waste—such as fabric scraps and discarded clothing—into value-added products. Safina Quilt applies the concepts of reduction, reuse, and upcycling throughout its production processes using quilting techniques, while simultaneously establishing an inclusive supply chain that engages local tailors, individuals with disabilities, and homemakers. This business model not only delivers economic gains by increasing profit margins and expanding market reach but also generates substantial social benefits by empowering vulnerable community groups. Although challenges remain, including limited access to supporting materials, constraints in production capacity, and insufficient digital marketing efforts, Safina Quilt demonstrates how MSMEs can successfully integrate environmental, economic, and social sustainability. Strengthening supply chain mechanisms, enhancing production capabilities, and improving digital marketing strategies are essential for scaling up and ensuring long-term business sustainability.